COVID-19: An Interdisciplinary Approach to Emergency Care, Laboratory Diagnostics, Pharmaceutical Management, Social Services, and Industrial Security - Sanad, Faisal Mohammed N Bin; Alotaibi, Ahmad Naif Helal; Hassan , Ali Abdu; Alsharari, Nawaf Hulayyil Suwayjan; Alameer, Adel Gassem Mohammad; Alsharari, Mazen Saeed Alturqi; Alali, Abdulellah Mokhlaf; Faqihi, Mohammed Shaker Mousa; Almaklhafi , Nada Saleh; Alonazi, Hayel Salem; Alsubaie, Alanoud Nasser; Daghriri, Hatim Yahya A; et al. (Journal of Ecohumanism, 2024)
Background: The COVID-19 pandemic, caused by SARS-CoV-2, has posed unprecedented global challenges, with over 601 million confirmed cases and 6.4 million deaths reported by September 2022. The virus's rapid mutation rate, emergence of variants of concern (VOCs), and socio-economic disparities have complicated its management. Concurrent outbreaks of other infectious diseases, environmental factors, and healthcare inequities have further exacerbated the crisis. Effective management requires an interdisciplinary approach, integrating emergency care, laboratory diagnostics, pharmaceutical interventions, social services, and industrial security. Aim: This article aims to provide a comprehensive overview of the interdisciplinary strategies employed to combat COVID-19, focusing on emergency care, diagnostic advancements, pharmaceutical management, vaccination, and the roles of social services and industrial security in mitigating the pandemic's impact. Methods: The study synthesizes data from global health organizations, clinical trials, and research studies. It examines diagnostic tools such as RT-PCR, RT-LAMP, and CRISPR-Cas12, therapeutic interventions like monoclonal antibodies and antiviral drugs, and vaccination strategies. The roles of social services in healthcare access, financial aid, and mental health support, alongside industrial security measures in workplace safety and supply chain management, are also analyzed. Results: Diagnostic advancements have improved COVID-19 detection, with RT-PCR remaining the gold standard. Therapeutic interventions, including monoclonal antibodies and antiviral drugs like molnupiravir, have shown efficacy in reducing mortality and hospitalization rates. Vaccination campaigns have achieved significant global coverage, with mRNA vaccines demonstrating high efficacy against multiple variants. Social services and industrial security have played critical roles in supporting vulnerable populations, ensuring workplace safety, and maintaining supply chain integrity. Conclusion: The COVID-19 pandemic underscores the importance of interdisciplinary collaboration in managing global health crises. Continued advancements in diagnostics, therapeutics, and vaccination, coupled with robust social services and industrial security measures, are essential for mitigating the pandemic's impact and preparing for future health emergencies.